A Novel Method of Early prediction of Packet Delay for Mobile Nodes with modified constraint violation Detection Algorithm (International Journal of Engineering and Computer Science, 2014)
Network delay is an important performance characteristic of a computer network or telecommunications network. The delay of a network specifies how long it takes for a bit of data to travel across the network from one node or endpoint to another. It is typically measured in multiples or fractions of seconds.The work presented here belongs to domain of wireless network , the real Time Early Prediction of network delay is done using the proposed constraint prediction Algorithm.Anew application is presented concerning the delivery delays of packets in GPRS network.The distributed monitoring of events from GPS device is considered for delay prediction in TCP/IP  network.Whenever the GPS device crosses the access point , the event dispatchfrom the device is monitored regularly for correct prediction.